1990
DOI: 10.1111/j.1574-6968.1990.tb04940.x
|View full text |Cite
|
Sign up to set email alerts
|

Formate dehydrogenase

Abstract: Formate is a substrate, or product, of diverse reactions catalyzed by eukaryotic organisms, eubacteria, and archaebacteria. A survey of metabolic groups reveals that formate is a common growth substrate, especially among the anaerobic eubacteria and archaebacteria. Formate also functions as an accessory reductant for the utilization of more complex substrates, and an intermediate in energy‐conserving pathways. The diversity of reactions involving formate dehydrogenases is apparent in the structures of electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
78
0
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(81 citation statements)
references
References 49 publications
1
78
0
2
Order By: Relevance
“…There are many reports on characterization of FDH from various microorganisms and higher plants and on the cloning and expression of their genes. [1][2][3][4][5] On the other hand, only two FODs have been purified from Debaryomyces vanrijiae MH201 and Aspergillus nomius IRI013 and characterized. [6][7][8] These FODs show similar UV-visible spectra, suggesting the presence of similar cofactors in their molecules.…”
mentioning
confidence: 99%
“…There are many reports on characterization of FDH from various microorganisms and higher plants and on the cloning and expression of their genes. [1][2][3][4][5] On the other hand, only two FODs have been purified from Debaryomyces vanrijiae MH201 and Aspergillus nomius IRI013 and characterized. [6][7][8] These FODs show similar UV-visible spectra, suggesting the presence of similar cofactors in their molecules.…”
mentioning
confidence: 99%
“…While the oxidation of formate by numerous organisms dunng anaerobiosis is common (15), the assimilation of formate is usually an aerobic process (1,18,26). In those cases in which synthetic purple non-sulfur bacteria (13,40), the latter requiring light, are able to grow on methanol or formate anaerobically.…”
mentioning
confidence: 99%
“…Many FDHs have been purified from various microorganisms and higher plants and well characterized. [1][2][3][4][5] Sakai et al reported that the main physiological role of FDH from Candida boidinii, a methylotrophic yeast, appears to be detoxification of formate and that the FDH appears to contribute to the energy yield. 6) On the other hand, there have been only two reports on the properties of FOD from Debaryomyces vanrijiae MH201 and Aspergillu.…”
mentioning
confidence: 99%